Celebrating Birthdays for Maril Turpin, Shirley Griffenhagen and Leslie Prusia at the Watkins' Home - Watkins, Howard::::::::: (1986)
Leslie Prusia gift of framed photograph of blooming dogwood tree; Maril Turpin on right